(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Polycyclic aromatic hydrocarbons (PAHs) are widely distributed in the environment and may persist for extended periods of time. PAHs are one of the most important classes of persistent organic contaminants. High molecular weight (HMW) PAHs (compounds containing four or more fused benzene rings) are generally recalcitrant to microbial attack. Until recently, only a few genera of bacteria have been isolated with the ability to utilize four-ring PAHs as sole carbon and energy sources. Because of the toxic, mutagenic, and carcinogenic characteristics of some, PAHs have been studied extensively by many scientists around the word. This paper presents research results, where 10 microbial strains belonging to genus Arthrobacter sp. and obtained from culture collection of JSC "Biocentras"were tested for the best biodegradation of HMW PAH pyrene. Pyrene degradation experiments were conducted in liquid mineral medium. Pyrene concentration was 0. 2 mg/mL at the beginning of degradation experiments. After 72 h incubation with ten Arthrobacter sp. strains, gas chromatography analysis revealed that highest pyrene degradation (19%) was reached by Arthrobacter sp. NJ5 strain. The effect of medium pH, pyrene concentration and temperature on the intensity of the degradation by the most active strain Arthrobacter NJ5 was investigated.